HUBUNGAN DUKUNGAN SUAMI DENGAN MINAT IBU MENGGUNAKAN KB IUD DI PUSKESMAS 23 ILIR PALEMBANG TAHUN 2024 - Chantika Putri, Maya; Ismawati Hakim, Riska; Vicky Yulivantina, Eka (STIKES Panca Bhakti Pontianak, 2025)
Background: The World Health Organization (WHO) reports increased global contraceptive use, with a 54% rise in modern methods like pills, injections, and IUDs since 2018. In Indonesia, IUD usage has grown, yet only 8% of users opt for them, indicating low interest compared to other methods. Spousal support significantly influences contraceptive use. This study will examine the link between spousal support and maternal interest in IUDs at Puskesmas 23 Ilir Palembang in 2023. Research Method: The research used an analytical survey with a cross-sectional design, focusing on family planning acceptors at Puskesmas 23 Ilir Palembang. A purposive sample of 35 respondents was selected, and data was collected via a questionnaire. Univariate analysis was conducted using frequency distribution tables, and bivariate analysis was performed with Fisher's Exact Test to assess dependencies. Results: Frequency distribution: Most of them did not receive support from their husbands, 22 respondents (62.9%), most of them had little interest in using IUD contraceptives, 14 respondents (40%). The statistical test results showed p.value = 0.001. Conclusion: There is a significant association between husband's support and mother's interest in using IUD contraception in Puskesmas 23 Ilir Palembang in 2024